Answer:
i) [tex]cosec0 = \frac{hypotenuse}{opposite side} = \frac{53}{45}[/tex]
ii) [tex]sec0 = \frac{hypotenuse}{adjacent side} = \frac{53}{28}[/tex]
Step-by-step explanation:
Step(i):-
Given that
[tex]cot 0 = \frac{28}{45} = \frac{adjacentside}{opposite side}[/tex]
Hypotenuse AC² = AB²+BC²
⇒ AC² = 45²+28² = 2809
⇒ AC = √2809
⇒ AC = 53
Hypotenuse AC =53
Step(ii):-
i) [tex]cosec0 = \frac{hypotenuse}{opposite side} = \frac{53}{45}[/tex]
ii) [tex]sec0 = \frac{hypotenuse}{adjacent side} = \frac{53}{28}[/tex]